Shariah compliance space planning for hotel room design - Saifuddin, Syala; Othman, Rashidi; Md Hisham, Muhammad Hafizuddin Akmal; Jasmani, Ismail; Abdul Majid, Noor Hanita (World Academy of Science, Engineering and Technology (W A S E T), 2015)
This paper illustrates the background of various concepts, approaches, terminologies used to describe the basic framework of an Islamic Hotel Room Design. This paper reviews the theoretical views in establishing a suitable and optimum environment for Muslim as well as non-Muslim guests in hotel rooms according to shariah. It involves a few research methodologies that requires the researcher to study on a few characteristics needed to create more efficient rooms in terms of social interaction, economic growth and other tolerable elements. This paper intends on revealing the elements that are vital and may contribute for hotels achieving a more conclusive research on space planning for hotel rooms focusing on shariah and Muslim guests. Malaysia is an Islamic country and has billions of tourists coming over for business and recreational purposes. Therefore, having a righteous environment that best suit this target user is important in terms of generating the economy as well as providing a better understanding to the community on the benefits of applying these qualities in a conventional resort design.